Strong Subordination for E -valent Functions Involving the Operator Generalized Srivastava-Attiya (Baghdad Science Journal, 2020)
Some relations of inclusion and their properties are investigated for functions of type " -valent that involves the generalized operator of Srivastava-Attiya by using the principle of strong differential subordination.